ANALISIS FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, INCOME, LOCUS OF CONTROL, FINANCIAL MANAGEMENT BEHAVIOR MASYARAKAT KOTA KEDIRI - BUDIONO, EKO (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to determine the effect of financial knowledge, financial attitude, personal income, locus of control on the financial management behavior. The type of quantitative research with 387 respondents used nonprobability sampling techniques, namely snowball sampling and purposive sampling. The object of this research is the people of Kediri City. Data obtained by interviews, and providing questionnaires offline and online. The data analysis technique uses multiple linear regression analysis with IBM SPSS version 18. The results of this study state that personal income does not affect the financial management behavior because both women and men have the same opportunity and ability to manage their finances. Financial knowledge affects the financial management behavior because someone with high knowledge, financial management will be better, while someone with low financial knowledge, financial management will also be bad. Financial attitude is influential because someone has a good and responsible financial attitude, tends to be good in financial management. Locus of control has an effect because someone who has high internal and external self-control will have good financial control. Keywords: financial attitude; financial knowledge; financial management behaviour personal income; locus of control